Positive electrode active material, and positive electrode and lithium secondary battery comprising same

By adopting lithium transition metal composite oxide in the form of a single particle, combined with specific sintering and calendering treatment, the problem of cracks in high-nickel positive electrode active materials in lithium secondary batteries is solved, and higher energy density and capacity characteristics are achieved.

CN119698701APending Publication Date: 2025-03-25LG CHEM LTD

Patent Information

Application Number
CN202380059530.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-08
Filing Date
2023-09-05
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

High nickel positive electrode active materials are prone to cracks during the charging and discharging of lithium secondary batteries, resulting in the inability to fully reach the electrolyte, reducing battery life and increasing resistance.

Method used

A lithium transition metal composite oxide in the form of a single particle, containing nickel, cobalt and manganese, is used to apply force to form particles through an automatic granular press, and a positive electrode active material with D50 of more than 5 μm is prepared through a specific sintering process to ensure that the rolling density reaches 3.56g/cm3 or more.

Benefits of technology

By controlling the average particle size and particle size distribution of the positive electrode active material, the occurrence of cracks is reduced, the rolling density is improved, and the energy density and capacity characteristics of lithium secondary batteries are increased.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119698701A_ABST
    Figure CN119698701A_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material, and a positive electrode and a lithium secondary battery comprising the same, and relates to a positive electrode active material comprising a lithium transition metal composite oxide in a single particle form, the lithium transition metal composite oxide in the single particle form containing nickel, cobalt and manganese, the lithium transition metal composite oxide contains 60 mol% or more of nickel with respect to the total transition metal, and has a D50 of 5 [mu] m or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] [CROSS-REFERENCE TO RELATED APPLICATIONS]

[0002] This application claims priority to Korean Patent Application No. 10-2022-0113918, filed on September 8, 2022, the disclosure of which is incorporated herein by reference. Technical Field

[0003] The present invention relates to a positive electrode active material, a positive electrode comprising the same, and a lithium secondary battery. Background Art

[0004] With the recent technological development of electric vehicles, the demand for high-capacity secondary batteries is increasing, and accordingly, research on high-nickel (high Ni) positive electrode active materials having excellent capacity characteristics is being actively conducted.

[0005] For a high nickel positive active material formed with a secondary particle structure in which primary particles are aggregated, structural degradation occurs during the charge and discharge of a lithium secondary battery, and a relatively large change occurs in the lattice structure constant, that is, a relatively large volume change occurs in the unit lattice. This volume change causes cracks in the positive active material. In addition, cracks may also occur in the positive active material due to pressure even during electrode rolling.

[0006] As a result, cracks occurring in the high-nickel positive electrode active material become more serious during the charge and discharge process of the lithium secondary battery, and therefore, since the cracks act as voids that the electrolyte may not reach or reduce conductivity, it reduces the life characteristics of the lithium secondary battery or becomes a factor that increases resistance.

[0007] As a method to minimize the occurrence of cracks in the secondary particle structure, attempts are being made to prepare a single-particle form of a positive electrode active material. Typically, in order to prepare a single-particle form of a positive electrode active material, after a transition metal hydroxide prepared by a coprecipitation method is mixed with a lithium compound and an expanded secondary particle is first prepared by oversintering the mixture, the secondary particle is ground to prepare it in a single particle form. However, in the case of preparing a single-particle form of a positive electrode active material as described above, since the diameter of the primary particles constituting the secondary particles is uneven, there is a problem in that the particle size distribution of the positive electrode active material in the single particle form obtained after grinding increases. However, since the performance and electrode design of lithium secondary batteries vary greatly depending on the particle size distribution of the positive electrode active material, it is very important to control the particle size distribution and average particle size of the positive electrode active material.

[0008] [Prior art literature]

[0009] [Patent Document]

[0010] (Patent Document 1) KR 10-1785262 B1

[0011] (Patent Document 2) KR 10-2017-0119573 A Summary of the invention

[0012] Technical issues

[0013] One aspect of the present invention provides a positive electrode active material in the form of a single particle in which an average particle size is controlled while having a negative skewness.

[0014] Another aspect of the present invention provides a positive electrode and a lithium secondary battery, wherein the calendering density during the preparation of the positive electrode is improved by including a positive electrode active material in a single particle form.

[0015] Technical Solution

[0016] In order to solve the above-mentioned task, the present invention provides a method for preparing a positive electrode active material, a positive electrode active material prepared therefrom, and a positive electrode and a lithium secondary battery comprising the same.

[0017] (1) The present invention provides a positive electrode active material, the positive electrode active material comprising a lithium transition metal composite oxide in the form of a single particle, the lithium transition metal composite oxide in the form of a single particle containing nickel, cobalt and manganese, wherein the lithium transition metal composite oxide contains 60 mol % or more of nickel relative to all transition metals, D 50 5 μm or more, and when pellets are formed by applying force until the force reaches 9,000 kgf using an automatic pelletizing machine, the calendering density calculated by Formula 3 is 3.56 g / cm 3 above.

[0018] [Formula 3]

[0019] Calendering density (g / cm 3 ) = positive electrode active material weight (g) / particle volume (cm 3 )

[0020] (2) The present invention provides the positive electrode active material described in (1) above, wherein the lithium transition metal composite oxide in the form of a single particle is a single particle or a secondary particle in which 10 or less primary particles are aggregated.

[0021] (3) The present invention provides the positive electrode active material described in (1) or (2) above, wherein the lithium transition metal composite oxide has an average composition represented by Chemical Formula 1.

[0022] [Chemical formula 1]

[0023] Lix Ni a Co b Mn c M 1 d O2

[0024] In Chemical Formula 1, M 1 is at least one selected from the group consisting of aluminum (Al), zirconium (Zr), boron (B), tungsten (W), molybdenum (Mo), chromium (Cr), niobium (Nb), magnesium (Mg), hafnium (Hf), tantalum (Ta), lanthanum (La), titanium (Ti), strontium (Sr), barium (Ba), cerium (Ce), fluorine (F), phosphorus (P), sulfur (S), and yttrium (Y), and 0.9 ≤ x ≤ 1.3, 0.6 ≤ a < 1.0, 0 < b < 0.4, 0 < c < 0.4, 0 ≤ d ≤ 0.2 and a + b + c + d = 1.

[0025] (4) The present invention provides the positive electrode active material described in (3) above, wherein x is in the range of 0.9 to 1.1.

[0026] (5) The present invention provides the positive electrode active material described in any one of (1) to (4) above, wherein D 50 is in the range of 5 μm to 9 μm.

[0027] (6) The present invention provides the positive electrode active material described in any one of (1) to (5) above, wherein the calendering density is in the range of 3.56 g / cm 3 to 3.80 g / cm 3 range.

[0028] (7) The present invention provides the positive electrode active material described in any one of (1) to (6) above, wherein the mode in the volume cumulative distribution according to the particle size is greater than D 50 .

[0029] (8) The present invention provides the positive electrode active material described in (7) above, wherein the negative skewness value calculated by Formula 1 of the positive electrode active material is greater than 0.

[0030] [Formula 1]

[0031] Negative skewness = (mode - D 10 ) / D 50

[0032] (9) The present invention provides the positive electrode active material described in (8) above, wherein the negative skewness value is in the range of 0.40 to 0.75.

[0033] (10) The present invention provides a positive electrode, the positive electrode comprising the positive electrode active material described in any one of (1) to (9).

[0034] (11) The present invention provides a lithium secondary battery, the lithium secondary battery comprising:

[0035] (10) the positive electrode;

[0036] negative electrode;

[0037] a separator disposed between the positive electrode and the negative electrode; and

[0038] Electrolytes.

[0039] Beneficial Effects

[0040] Since the positive electrode active material of the present invention is in the form of a single particle, in which the average particle size is controlled while having a negative skewness, when a positive electrode is prepared by including the positive electrode active material, the energy density of the lithium secondary battery can be increased by improving the calendering density, and accordingly, the capacity characteristics are improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 is a graph showing the cumulative volume distribution according to the particle size of each positive electrode active material prepared in Examples of the present invention and Comparative Examples.

[0042] Figure 2 is a scanning electron microscope image of the positive electrode active material prepared in Example 1 of the present invention.

[0043] Figure 3 is a scanning electron microscope image of the positive electrode active material prepared in Example 2 of the present invention.

[0044] Figure 4 is a scanning electron microscope image of the positive electrode active material prepared in Example 3 of the present invention.

[0045] Figure 5 is a scanning electron microscope image of the positive electrode active material prepared in Example 4 of the present invention.

[0046] Figure 6 is a scanning electron microscope image of the positive electrode active material prepared in Example 5 of the present invention.

[0047] Figure 7 is a scanning electron microscope image of the positive electrode active material prepared in Example 6 of the present invention.

[0048] Figure 8 is a scanning electron microscope image of the positive electrode active material prepared in Example 7 of the present invention.

[0049] Fig. 9 is a scanning electron microscope image of the positive electrode active material prepared in Comparative Example 1 of the present invention.

[0050] Fig.10 is a scanning electron microscope image of the positive electrode active material prepared in Comparative Example 2 of the present invention.

[0051] Fig.11 is a scanning electron microscope image of the positive electrode active material prepared in Comparative Example 3 of the present invention.

[0052] Fig.12 is a scanning electron microscope image of the positive electrode active material prepared in Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0053] Hereinafter, the present invention will be described in more detail to make the present invention more clearly understood.

[0054] It should be understood that the words or terms used in this specification and claims should not be interpreted as the meanings defined in commonly used dictionaries, and it should be further understood that, based on the principle that the inventors can appropriately define the meanings of words or terms to best explain the present invention, the words or terms should be interpreted as having meanings that are consistent with their meanings in the context of the relevant fields and technical ideas of the present invention.

[0055] In the present invention, the expression "primary particle" means the smallest particle unit distinguished as one bulk when a cross section of a positive electrode active material is observed by a scanning electron microscope (SEM), wherein it may be composed of a plurality of crystal grains.

[0056] In the present invention, the expression "secondary particles" refers to a secondary structure formed by aggregation of a plurality of primary particles. The average particle diameter of the secondary particles can be measured using a particle size analyzer.

[0057] The term "D 10 ”, “D 50 ” and “D 90 ” respectively represent the particle size at 10% of the volume cumulative distribution of particle size (D 10 ), particle size at 50% (D 50 ) and the particle size at 90% (D 90 After the measurement target powder is dispersed in a dispersion medium, the dispersion medium is introduced into a commercially available laser diffraction particle size measuring instrument (e.g., Mastersizer 3000 of Malvern Panalytical Ltd.), and the volume cumulative distribution according to the particle size is calculated by measuring the difference in the diffraction pattern due to the particle size when the particles pass through the laser beam, and the particle size at 10%, 50%, and 90% of the volume cumulative distribution according to the particle size can be measured by using the measuring instrument. 10 , D 50 and D 90In addition, D in the present invention 50 It can be expressed as the average particle size.

[0058] The expression "single particle form" in the present invention has the following meanings: the particles of the positive electrode active material and / or the lithium transition metal composite oxide are both single particles and in which 2 to 10 particles are aggregated. That is, in the single particle form of the positive electrode active material and / or the single particle form of the lithium transition metal composite oxide of the present invention, the particles of the positive electrode active material and / or the lithium transition metal composite oxide may include at least one selected from the group consisting of single particles and particles in which 2 to 10 particles are aggregated.

[0059] Positive electrode active material

[0060] The invention provides a positive electrode active material.

[0061] According to one embodiment of the present invention, the positive electrode active material comprises a lithium transition metal composite oxide in the form of a single particle, wherein the lithium transition metal composite oxide contains nickel, cobalt and manganese, wherein the lithium transition metal composite oxide contains 60 mol % or more of nickel relative to the total transition metals, D 50 5 μm or more, and when pellets are formed by applying force until the force reaches 9,000 kgf using an automatic pelletizing machine, the calendering density calculated by the following formula 3 may be 3.56 g / cm 3 above.

[0062] [Formula 3]

[0063] Calendering density (g / cm 3 ) = positive electrode active material weight (g) / particle volume (cm 3 )

[0064] According to an embodiment of the present invention, the positive electrode active material may include a lithium transition metal composite oxide in the form of single particles. As a specific example, the lithium transition metal composite oxide in the form of single particles may be single particles or secondary particles in which 10 or fewer primary particles are aggregated. Regarding conventional positive electrode active materials in the form of secondary particles in which more than 10 primary particles are aggregated, it is necessary to increase the porosity to minimize cracks caused by the pressure during rolling for preparing the electrode, and this ultimately causes a decrease in the energy density of the lithium secondary battery. However, in the case where the lithium transition metal composite oxide has the form of single particles or secondary particles in which 10 or fewer primary particles are aggregated as in the positive electrode active material of the present invention, when the lithium secondary battery is charged and discharged, cracks caused by volume changes in the unit lattice can be minimized, and in particular, cracks caused by the pressure during rolling for preparing the electrode can be minimized. Therefore, in the case of using the positive electrode active material of the present invention, since rolling can be performed with a lower porosity during rolling for preparing the electrode, the energy density of the lithium secondary battery can be improved.

[0065] According to an embodiment of the present invention, the lithium transition metal composite oxide may be a high-nickel type lithium transition metal composite oxide, the lithium transition metal composite oxide contains nickel, and based on all transition metals, the nickel (Ni) content is 60 mol% or more. In this case, a high energy density can be ensured due to the high nickel content.

[0066] According to an embodiment of the present invention, the lithium transition metal composite oxide may have an average composition represented by the following Chemical Formula 1.

[0067] [Chemical Formula 1]

[0068] Li x Ni a Co b Mn c M 1 d O2

[0069] In Chemical Formula 1, M 1 is at least one selected from the group consisting of: aluminum (Al), zirconium (Zr), boron (B), tungsten (W), molybdenum (Mo), chromium (Cr), niobium (Nb), magnesium (Mg), hafnium (Hf), tantalum (Ta), lanthanum (La), titanium (Ti), strontium (Sr), barium (Ba), cerium (Ce), fluorine (F), phosphorus (P), sulfur (S), and yttrium (Y), and 0.9 ≤ x ≤ 1.3, 0.6 ≤ a < 1.0, 0 < b < 0.4, 0 < c < 0.4, 0 ≤ d ≤ 0.2 and a + b + c + d = 1.

[0070] According to an embodiment of the present invention, M in Chemical Formula 11 It may be a doping element, which may be contained in the lithium transition metal composite oxide, and may be appropriately selected according to needs.

[0071] According to one embodiment of the present invention, in Chemical Formula 1, x is the molar ratio of lithium to transition metal in the lithium transition metal composite oxide, wherein x may be greater than 0.9, greater than 0.95, or greater than 1.0, and may also be less than 1.1, less than 1.07, less than 1.05, or less than 1.03.

[0072] According to one embodiment of the present invention, in Chemical Formula 1, a, b, c and d may be nickel (Ni), cobalt (Co), manganese (Mn) and doping element (Mn) in transition metals, respectively. 1 ). As a specific example, a is the mole fraction of nickel (Ni) in the transition metal, wherein a may be 0.6 or more, 0.7 or more, 0.8 or more, 0.85 or more, 0.88 or more, 0.90 or more, 0.91 or more, 0.92 or more, 0.93 or more, 0.94 or more, 0.95 or more, or 0.96 or more, and may be less than 1.0, 0.99 or less, 0.98 or less, 0.97 or less, or 0.96 or less in addition. In addition, b is the mole fraction of cobalt (Co) in the transition metal, wherein b may be greater than 0, 0.01 or more, 0.02 or more, or 0.03 or more, and may be less than 0.4, 0.3 or less, 0.2 or less, 0.1 or less, 0.09 or less, 0.08 or less, 0.07 or less, 0.06 or less, or 0.05 or less in addition. c is the molar fraction of manganese (Mn) in the transition metal, wherein c may be greater than 0, greater than 0.01, or greater than 0.05, and may also be less than 0.4, less than 0.3, less than 0.2, less than 0.1, less than 0.09, less than 0.08, less than 0.07, less than 0.06, or less than 0.05. d is the molar fraction of the doping element (Mn) in the transition metal. 1 ), wherein d may be 0, 0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, 0.10 or more, 0.11 or more, 0.12 or more, 0.13 or more, 0.14 or more, 0.15 or more, 0.16 or more, 0.17 or more, 0.18 or more, or 0.19 or more. , and additionally can be less than 0.20, 0.19 or less, 0.18 or less, 0.17 or less, 0.16 or less, 0.15 or less, 0.14 or less, 0.13 or less, 0.12 or less, 0.11 or less, 0.10 or less, 0.09 or less, 0.08 or less, 0.07 or less, 0.06 or less, 0.05 or less, 0.04 or less, 0.03 or less, 0.02 or less, or 0.01 or less.

[0073] According to one embodiment of the present invention, D of the positive electrode active material 50 Conventionally, when preparing a single-particle positive electrode active material, since after a precursor in the form of a hydroxide is mixed with a lithium compound and expanded secondary particles are prepared by over-sintering the mixture, the secondary particles are ground to prepare a single-particle positive electrode active material, a single-particle positive electrode active material is prepared, as D 50 The particles are small particles of about 1 μm to 4 μm, and therefore, there is an increase in the D of the positive electrode active material in the form of a single particle. 50 However, since the positive electrode active material according to the present invention is prepared by the method for preparing the positive electrode active material as described later, D 50 The cathode active material of the present invention may be 5 μm or larger and be in the form of a single particle. 50 5 μm or more, and in the form of a single particle, it is possible to further minimize the occurrence of cracks in the positive electrode active material, and in terms of improving the rolling density, it is comparable to D 50 The positive electrode active material of the present invention is more advantageous than a single particle form of a small particle of about 1 μm to 4 μm. That is, the positive electrode active material of the present invention is characterized in that it is in the form of a single particle and D 50 As a specific example, the D of the positive electrode active material 50 It may be 5 μm or more, 5.1 μm or more, 5.2 μm or more, 5.3 μm or more, 5.4 μm or more, 5.5 μm or more, 5.6 μm or more, 5.7 μm or more, 5.8 μm or more, 5.9 μm or more, 6.0 μm or more, 6.1 μm or more, 6.2 μm or more, 6.3 μm or more, 6.4 μm or more, 6.5 μm or more, 6.6 μm or more, 6.7 μm or more, 6.8 μm or more, 6.9 μm or more, or 7.0 μm or more. In addition, when the positive electrode active material is mixed with D 50 The positive electrode active material is distinguished by the secondary particle form of large particles of about 10 μm or more. 50 It may be 9 μm or less, 8.9 μm or less, 8.8 μm or less, 8.7 μm or less, 8.6 μm or less, 8.5 μm or less, 8.4 μm or less, 8.3 μm or less, 8.2 μm or less, 8.1 μm or less, 8.0 μm or less, 7.9 μm or less, 7.8 μm or less, 7.7 μm or less, 7.6 μm or less, 7.5 μm or less, 7.4 μm or less, 7.3 μm or less, 7.2 μm or less, 7.1 μm or less, 7.0 μm or less, or 6.5 μm or less. In the present invention, in order to obtain the above-mentioned D 50The positive electrode active material with a single particle size can be distinguished from the positive electrode active material with a small particle size and the positive electrode active material with a large particle size, and the positive electrode active material can be referred to as a positive electrode active material with a medium-sized single particle.

[0074] According to one embodiment of the present invention, when particles are formed by applying force until the force reaches 9,000 kgf using an automatic pelletizer, the calendering density of the positive electrode active material calculated by Formula 3 may be 3.56 g / cm 3 In this case, when a positive electrode is formed by using a positive electrode active material alone or by mixing a positive electrode active material with a small-particle size or large-particle size positive electrode active material, the porosity of the positive electrode can be further reduced by minimizing the occurrence of cracks due to rolling, and therefore, since a larger amount of positive electrode active material can be included in the same volume of the positive electrode active material layer, the energy density of the lithium secondary battery can be further improved.

[0075] According to one embodiment of the present invention, the calendering density of the positive electrode active material must be 3.56 g / cm 3 This is the minimum standard for achieving the effect according to the present invention, where the calendering density must be 3.56 g / cm 3 As a specific example, the calendering density of the positive electrode active material can be 3.57 g / cm 3 Above, 3.58g / cm 3 Above, 3.59g / cm 3 Above, 3.60g / cm 3 Above, 3.61g / cm 3 Above, 3.62g / cm 3 Above, 3.63g / cm 3 Above, 3.64g / cm 3 Above, 3.65g / cm 3 Above, 3.66g / cm 3 Above or 3.67g / cm 3 As described above, since the calendering density can be significantly improved within this range during the preparation of the positive electrode, the energy density of the lithium secondary battery can be increased, and thus the capacity characteristics can be further improved. In addition, the calendering density of the positive electrode active material can be 3.80 g / cm 3 Below, 3.75g / cm 3 Below, 3.74g / cm 3 Below, 3.73g / cm 3 Below or 3.72g / cm 3 the following.

[0076] According to one embodiment of the present invention, the positive electrode active material may be one of the following: wherein, in particular, in addition to the nickel content, D 50 In addition to the calendering density, the volume cumulative distribution of the positive electrode active material particles according to the particle size is also adjusted. As a specific example, for the positive electrode active material, the mode in the volume cumulative distribution of the positive electrode active material particles according to the particle size can be greater than D 50 .

[0077] In the positive electrode active material which is an aggregate of a plurality of particles constituting the volume cumulative distribution according to the particle size, the mode in the volume cumulative distribution according to the particle size as in the positive electrode active material of the present invention is greater than D 50 In the case of, since the amount of fine powder with a relatively small particle size is high, when the positive electrode active material layer is formed by using the positive electrode active material, the pores between the positive electrode active material particles can be minimized, and therefore, a larger amount of positive electrode active material particles can be contained in the same volume to ensure a higher energy density. Therefore, even if the D of the positive electrode active material 50 The same, since the energy density is based on the mode and D in the volume cumulative distribution according to the particle size 50 The difference between the nickel content and D 50 In addition to the calendering density, the positive electrode active material according to the present application can be obtained by adjusting the mode in the volume cumulative distribution according to the particle size to be greater than D 50 To further improve the energy density of lithium secondary batteries.

[0078] According to one embodiment of the present invention, the negative skewness value of the positive electrode active material calculated by the following Formula 1 may be greater than 0.

[0079] [Formula 1]

[0080] Negative skewness = (mode - D 10 ) / D 50

[0081] Generally, skewness is a statistical measure of the asymmetry of a specific distribution, wherein if the skewness value is positive, it is expressed as positive skewness, and if the skewness value is negative, it is expressed as negative skewness. However, since positive skewness and negative skewness expressed by conventional methods are expressed in the form of a cube that deviates from the mean, the skewness value becomes larger as the skewness increases, and therefore, it is inappropriate to determine the amount of fine powder of the positive electrode active material in the present invention. Therefore, in the present invention, negative skewness is newly defined and expressed by Formula 1 above. According to Formula 1 above, the negative skewness in the present invention is expressed as the mode and D 10 The difference between 50 By using D 50 Compare the mode with D corresponding to the fine powder region10 By comparing the difference between φ and φ, the amount of fine powder of the positive electrode active material, which is an aggregate of a plurality of particles constituting the volume cumulative distribution according to the particle size, can be indirectly confirmed.

[0082] According to one embodiment of the present invention, the negative skewness value of the positive electrode active material calculated by Formula 1 can be greater than 0, greater than 0.10, greater than 0.20, greater than 0.30, greater than 0.40 or greater than 0.45, and can also be less than 0.75, less than 0.70, less than 0.65, less than 0.60, less than 0.59, less than 0.58, less than 0.57, less than 0.56 or less than 0.55. Within this range, the amount of fine powder with a relatively small particle size can be appropriately adjusted to minimize cracks caused by pressure during rolling for preparing the electrode, maximize the energy density of the lithium secondary battery, and ensure capacity characteristics.

[0083] According to one embodiment of the present invention, the mode in the volume cumulative distribution according to the particle size of the positive electrode active material may be 5.5 μm or more, 5.6 μm or more, 5.7 μm or more, 5.8 μm or more, 5.9 μm or more, 6.0 μm or more, 6.1 μm or more, 6.2 μm or more, 6.3 μm or more, 6.4 μm or more, 6.5 μm or more, 6.6 μm or more, 6.7 μm or more, 6.8 μm or more, 6.9 μm or more, 7.0 μm or more, 7.1 μm or more, 7.2 μm or more, 7.3 μm or more, 7.4 μm or more or 7.5 μm or more, and may additionally be 9.5 μm or less, 9.4 μm or less, 9.3 μm or less, 9.2 μm or less, 9.1 μm or less, 9.0 μm or less, 8.9 μm or less, 8.8 μm or less, 8.7 μm or less, 8.6 μm or less, 8.5 μm or less, 8.4 μm or less, 8.3 μm or less, 8.2 μm or less, 8.1 μm or less, 8.0 μm or less, 7.9 μm or less, 7.8 μm or less, 7.7 μm or less, 7.6 μm or less, 7.5 μm or less, or 7.0 μm or less, except for the nickel content, D 50 In addition to the rolling density, within this range, the energy density of the lithium secondary battery can be further improved.

[0084] According to one embodiment of the present invention, D of the positive electrode active material in the volume cumulative distribution according to the particle size 10 It can be 3.0μm or more, 3.1μm or more, 3.2μm or more, 3.3μm or more, 3.4μm or more or 3.5μm or more, and can also be 6.0μm or less, 5.5μm or less or 5.0μm or less, and the energy density of the lithium secondary battery can be further improved by adjusting the fine powder size within this range.

[0085] According to one embodiment of the present invention, the mode and D of the positive electrode active material 50 The difference may be 1.0 μm or less, 0.9 μm or less, 0.8 μm or less, 0.7 μm or less, 0.6 μm or less, or 0.5 μm or less, and may also be 0.1 μm or more, 0.2 μm or more, 0.3 μm or more, or 0.4 μm or more. In addition to the nickel content, D 50 In addition to the rolling density, within this range, the energy density of the lithium secondary battery can be further improved.

[0086] Method for preparing positive electrode active material

[0087] The present invention provides a method for preparing a positive electrode active material, wherein the method is used to prepare the positive electrode active material.

[0088] According to one embodiment of the present invention, a method for preparing a positive electrode active material comprises the following steps:

[0089] A positive electrode active material precursor containing nickel, cobalt and manganese and containing 60 mol % or more of nickel in transition metal is mixed with a lithium raw material and subjected to primary sintering to prepare a pre-sintered product (S10); and

[0090] The pre-sintered product prepared in step (S10) is subjected to secondary sintering to prepare a lithium transition metal composite oxide in the form of single particles (S20),

[0091] The secondary sintering can be performed at a lower temperature than the primary sintering.

[0092] As described above, since the secondary sintering is performed at a lower temperature than the primary sintering, the positive electrode active material can be prepared. 50 5 μm or more, and when pellets are formed by applying force until the force reaches 9,000 kgf using an automatic pelletizing machine, the calendering density calculated by Formula 3 is 3.56 g / cm 3 above.

[0093] According to an embodiment of the present invention, the temperature difference between the first sintering in step (S10) and the second sintering in step (S20) may be 10 °C or more, 20 °C or more, 30 °C or more, 40 °C or more, or 50 °C or more, and may additionally be 300 °C or less, 250 °C or less, 200 °C or less, 150 °C or less, or 100 °C or less. As a specific example, the first sintering in step (S10) may be performed at a temperature of 800 °C to 1,000 °C. As a more specific example, the first sintering in step (S10) may be performed within a temperature range of 800 °C to 1,000 °C, 830 °C to 950 °C, or 850 °C to 900 °C. Additionally, the second sintering in step (S20) may be performed at a temperature of 600 °C to 900 °C. As a more specific example, the second sintering in step (S20) may be performed within a temperature range of 600 °C to 900 °C, 650 °C to 850 °C, or 700 °C to 800 °C.

[0094] According to an embodiment of the present invention, in the pre-sintered product prepared by the first sintering in step (S10), since the particles may aggregate with each other, the second sintering in step (S20) may be performed on the ground product obtained by grinding the pre-sintered product prepared in step (S10).

[0095] According to an embodiment of the present invention, the precursor of the cathode active material containing nickel, cobalt, and manganese and containing 60 mol% or more of nickel in the transition metal may be a transition metal hydroxide or a transition metal oxide. As a specific example, the transition metal hydroxide may have an average composition represented by Chemical Formula 2 below, and the transition metal oxide may have an average composition represented by Chemical Formula 3 below.

[0096] [Chemical Formula 2]

[0097] Ni a’ Co b’ Mn c’ (OH)2

[0098] [Chemical Formula 3]

[0099] Ni a” Co b” Mn c” O

[0100] In Chemical Formula 2, 0.6 ≤ a' < 1.0, 0 < b' < 0.4, 0 < c' < 0.4, and a' + b' + c' = 1. In Formula 3, 0.6 ≤ a'' < 1.0, 0 < b'' < 0.4, 0 < c'' < 0.4, and a'' + b'' + c'' = 1.

[0101] According to one embodiment of the present invention, in Chemical Formula 2 and Chemical Formula 3, a', a", b', b", c' and c" may be mole fractions of nickel (Ni), cobalt (Co) and manganese (Mn) in the transition metal, respectively. As a specific example, a' or a" is the mole fraction of nickel (Ni) in the transition metal, wherein a' or a" may be 0.6 or more, 0.7 or more, 0.8 or more, 0.85 or more, 0.88 or more, 0.90 or more, 0.91 or more, 0.92 or more, 0.93 or more, 0.94 or more, 0.95 or more, or 0.96 or more, and may also be less than 1.0, 0.99 or less, 0.98 or less, 0.97 or less, or 0.96 or less. In addition, b b' or b" is the mole fraction of cobalt (Co) in the transition metal, wherein b' or b" may be greater than 0, greater than 0.01, greater than 0.02, or greater than 0.03, and may additionally be less than 0.4, less than 0.3, less than 0.2, less than 0.1, less than 0.09, less than 0.08, less than 0.07, less than 0.06, or less than 0.05. In addition, c' or c" is the mole fraction of manganese (Mn) in the transition metal, wherein c' or c" may be greater than 0, greater than 0.01, or greater than 0.05, and may additionally be less than 0.4, less than 0.3, less than 0.2, less than 0.1, less than 0.09, less than 0.08, less than 0.07, less than 0.06, or less than 0.05.

[0102] According to one embodiment of the present invention, the transition metal oxide can be prepared by sintering a transition metal hydroxide. As a specific example, the transition metal oxide can be prepared by sintering a transition metal hydroxide containing nickel, cobalt and manganese and containing 60 mol % or more of nickel in the transition metal in air or oxygen atmosphere (S1). In this case, the sintering in step (S1) can be carried out at a temperature of 800°C or more, as a specific example, at a temperature of 800°C or more, 850°C or more, 900°C or more, 950°C or more, or 1,000°C or more, and in addition, at a temperature of 1,200°C or less, 1,150°C or less, 1,100°C or less, or 1,050°C or less.

[0103] According to one embodiment of the present invention, from the viewpoint of ensuring a higher calendering density of the positive electrode active material of the medium-sized single particles according to the present invention, it may be more desirable to use a transition metal oxide as a nickel positive electrode active material precursor containing nickel, cobalt and manganese and containing 60 mol % or more of the transition metal.

[0104] According to one embodiment of the present invention, step (S1) can be performed by comprising the following steps:

[0105] mixing a transition metal hydroxide with a doping raw material (S1-1); and

[0106] The transition metal oxide (S1-2) is prepared by sintering the mixture mixed in the step (S1-1) in air or an oxygen atmosphere.

[0107] In this case, the doping raw material may include at least one doping element selected from the group consisting of Li, Al, Zr, B, W, Mo, Cr, Nb, Mg, Hf, Ta, La, Ti, Sr, Ba, Ce, F, P, S and Y.

[0108] According to one embodiment of the present invention, during the mixing of the positive electrode active material precursor and the lithium raw material in step (S10), the molar ratio (Li / M) of lithium (Li) of the lithium raw material to the transition metal (M) of the positive electrode active material precursor may be in the range of 0.9 to 1.3. As a specific example, Li / M may be 0.9 or more, 0.95 or more, or 1.0 or more, and may also be 1.1 or less, 1.07 or less, 1.05 or less, or 1.03 or less, and Li / M may be adjusted according to the nickel content in the transition metal.

[0109] positive electrode

[0110] The present invention provides a positive electrode, which comprises a positive electrode active material.

[0111] According to one embodiment of the present invention, a positive electrode may include a positive electrode collector and a positive electrode active material layer formed on the positive electrode collector, wherein the positive electrode active material layer may include the above-mentioned positive electrode active material.

[0112] According to one embodiment of the present invention, the positive electrode current collector may include a metal with high conductivity, and there is no particular limitation, as long as it is non-reactive within the voltage range of the battery and the positive electrode active material layer is easily adhered thereto. As the positive electrode current collector, for example, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used. In addition, the thickness of the positive electrode current collector can generally be 3 μm to 500 μm, and fine concavoconvexities can be formed on the surface of the current collector to improve the adhesion of the positive electrode active material. The positive electrode current collector can be used in various shapes such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc.

[0113] According to one embodiment of the present invention, if necessary, in addition to the positive electrode active material, the positive electrode active material layer may also optionally include a conductive material and a binder. In this case, based on the total weight of the positive electrode active material layer, the content of the positive electrode active material may be 80 wt % to 99 wt %, such as 85 wt % to 98.5 wt %, within which excellent capacity characteristics may be obtained.

[0114] According to one embodiment of the present invention, a conductive material is used to provide conductivity to the electrode, wherein any conductive material can be used without particular limitation, as long as it has suitable electronic conductivity and does not cause adverse chemical changes in the battery. Specific examples of conductive materials can be graphite, such as natural graphite or artificial graphite; carbon materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black and carbon fiber; powder or fiber of metals such as copper, nickel, aluminum and silver; conductive tubes, such as carbon nanotubes; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, and any one thereof or a mixture of two or more thereof can be used. Based on the total weight of the positive electrode active material layer, the content of the conductive material can be 0.1 wt % to 15 wt %.

[0115] According to one embodiment of the present invention, the binder improves the adhesion between the positive active material particles and the adhesion between the positive active material and the collector. Specific examples of the binder can be polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, polymethyl methacrylate, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid and polymers whose hydrogen is replaced by lithium (Li), sodium (Na) or calcium (Ca), or various copolymers thereof, and any one thereof or a mixture of two or more thereof can be used. Based on the gross weight of the positive active material layer, the content of the binder can be 0.1 wt % to 15 wt %.

[0116] According to one embodiment of the present invention, in addition to using the above-mentioned positive electrode active material, the positive electrode can also be prepared according to a typical method for preparing a positive electrode. Specifically, a positive electrode active material layer is coated on a positive electrode current collector, and then the positive electrode can be prepared by drying and calendering the coated positive electrode current collector, wherein the positive electrode active material layer is formed by dissolving or dispersing the positive electrode active material and optional binder and conductive material in a solvent, or the positive electrode active material layer can be formed by casting the composition on a separate carrier, and then the film separated from the carrier is stacked on the positive electrode current collector to prepare the positive electrode.

[0117] According to one embodiment of the present invention, the solvent may be a commonly used solvent in the art, and may include dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), dimethylformamide (DMF), acetone or water, and any one thereof or a mixture of two or more thereof may be used. Considering the coating thickness and manufacturing yield of the slurry, if the solvent can dissolve or disperse the positive electrode active material, the conductive material, the binder and the dispersant, and can allow for a viscosity that can provide excellent thickness uniformity during subsequent coating for preparing the positive electrode, the amount of the solvent may be sufficient.

[0118] Lithium secondary battery

[0119] The present invention provides a lithium secondary battery, which comprises a positive electrode.

[0120] According to one embodiment of the present invention, a lithium secondary battery may include a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte. In addition, the lithium secondary battery may further optionally include a battery container containing an electrode assembly of the positive electrode, the negative electrode and the separator, and a sealing member sealing the battery container.

[0121] According to one embodiment of the present invention, the negative electrode may include a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector.

[0122] According to one embodiment of the present invention, the negative electrode current collector is not particularly limited as long as it has high conductivity and does not cause adverse chemical changes in the battery, and can use, for example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc., and aluminum-cadmium alloy. In addition, the thickness of the negative electrode current collector can generally be 3 μm to 500 μm, and similar to the positive electrode current collector, fine concavoconvexities can be formed on the surface of the current collector to improve the adhesion of the negative electrode active material. The negative electrode current collector can be used in various shapes such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc.

[0123] According to one embodiment of the present invention, the negative electrode active material layer may optionally include a binder and a conductive material in addition to the negative electrode active material.

[0124] According to one embodiment of the present invention, a compound capable of reversibly inserting and deinserting lithium can be used as a negative electrode active material. Specific examples of negative electrode active materials can be: carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber and amorphous carbon; (semi)metallic materials that can be alloyed with lithium, such as silicon (Si), aluminum (Al), tin (Sn), lead (Pb), zinc (Zn), bismuth (Bi), indium (In), magnesium (Mg), gallium (Ga), cadmium (Cd), Si alloy, Sn alloy or Al alloy; (semi)metallic oxides that can be doped with lithium or not doped with lithium, such as SiO β (0<β<2), SnO2, vanadium oxide and lithium vanadium oxide; or a composite material comprising a (semi)metallic material and a carbonaceous material, such as a Si-C composite material or a Sn-C composite material, and any one thereof or a mixture of two or more thereof can be used. In addition, a metallic lithium film can be used as a negative electrode active material. In addition, both low-crystalline carbon and high-crystalline carbon can be used as carbon materials. Typical examples of low-crystalline carbon may be soft carbon and hard carbon, and typical examples of high-crystalline carbon may be irregular, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, condensed graphite, pyrolytic carbon, mesophase pitch-like carbon fibers, medium carbon phase carbon microbeads, mesophase pitch, and high-temperature sintered carbon such as coke derived from petroleum or coal tar pitch. Based on the total weight of the negative electrode active material layer, the content of the negative electrode active material may be 80% by weight to 99% by weight.

[0125] According to one embodiment of the present invention, the binder of the negative electrode active material layer is a component that contributes to the combination between the conductive material, the active material and the current collector, wherein the addition amount of the binder is generally 0.1 wt % to 10 wt % based on the total weight of the negative electrode active material layer. Examples of binders may be polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile rubber, fluororubber and various copolymers thereof.

[0126] According to one embodiment of the present invention, the conductive material of the negative electrode active material layer is a component for further improving the conductivity of the negative electrode active material, wherein the amount of the conductive material added may be 10% by weight or less, for example, 5% by weight or less, based on the total weight of the negative electrode active material layer. The conductive material is not particularly limited as long as it has conductivity and does not cause adverse chemical changes in the battery, and for example, conductive materials such as: graphite, such as natural graphite or artificial graphite; carbon black, such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black may be used; conductive fibers, such as carbon fibers or metal fibers; fluorocarbons; metal powders, such as aluminum powders and nickel powders; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxides; or polyphenylene derivatives.

[0127] According to one embodiment of the present invention, a negative electrode can be prepared by coating a composition for forming a negative electrode active material layer on a negative electrode collector and drying the coated negative electrode collector, wherein the composition for forming a negative electrode active material layer is prepared by dissolving or dispersing an optional binder and a conductive material and a negative electrode active material in a solvent, or the negative electrode can be prepared by casting the composition for forming a negative electrode active material layer on a separate carrier and then stacking the film separated from the carrier on the negative electrode collector.

[0128] According to one embodiment of the present invention, the separator separates the negative electrode and the positive electrode and provides a mobile path for lithium ions, wherein any separator can be used as a separator without particular limitation, as long as it is commonly used in lithium secondary batteries, in particular, a separator having high moisture retention capacity for electrolytes and low resistance to the transfer of electrolyte ions can be used. Specifically, a porous polymer film can be used, for example, a porous polymer film prepared by polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers, or a laminated structure with more than two layers thereof. In addition, a typical porous nonwoven fabric can be used, for example, a nonwoven fabric formed by high melting point glass fiber or polyethylene terephthalate fiber. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator with a monolayer or multilayer structure can be optionally used.

[0129] According to one embodiment of the present invention, the electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte or a molten inorganic electrolyte that can be used to prepare a lithium secondary battery, but the present invention is not limited thereto. As a specific example, the electrolyte may include an organic solvent and a lithium salt.

[0130] According to one embodiment of the present invention, any organic solvent can be used as an organic solvent without particular limitation, as long as it can be used as a medium through which ions participating in the electrochemical reaction of the battery can move. Specifically, the following substances can be used as organic solvents: ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; or carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol solvents such as ethanol and isopropanol; nitrile such as R-CN (wherein R is a linear, branched or cyclic C2-C20 hydrocarbon group, and may contain a double bond, an aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolanes; or cyclopentane sulfone. Among these solvents, carbonate solvents are preferred, and a mixture of a cyclic carbonate having high ionic conductivity and a high dielectric constant (e.g., ethylene carbonate or propylene carbonate) (which can increase the charge / discharge performance of the battery) and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred.

[0131] According to one embodiment of the present invention, a lithium salt can be used without particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the anion of the lithium salt can be at least one selected from the group consisting of: - , Cl - Br - ,I - 、NO3 - 、N(CN)2 - 、BF4 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N -, and the following may be used as the lithium salt: LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI or LiB(C2O4)2. The lithium salt may be used in a concentration range of 0.1M to 2.0M. When the concentration of the lithium salt is included in the above range, since the electrolyte may have appropriate conductivity and viscosity, excellent performance of the electrolyte may be obtained, and lithium ions may be efficiently moved.

[0132] According to one embodiment of the present invention, in order to improve the life characteristics of the battery, inhibit the reduction of the battery capacity and improve the discharge capacity of the battery, in addition to the above-mentioned electrolyte components, the electrolyte may further contain at least one additive, such as a halogenated alkylene carbonate compound, such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, (condensed) glycol dimethyl ether, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride. In this case, the content of the additive may be 0.1 wt % to 5 wt % based on the total weight of the electrolyte.

[0133] Since the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent capacity characteristics, output characteristics and life characteristics, the lithium secondary battery is suitable for portable devices such as mobile phones, notebook computers and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs) and electric vehicles (EVs).

[0134] The shape of the lithium secondary battery of the present invention is not particularly limited, but a cylindrical type using a can, a prismatic type, a pouch type, or a coin type may be used.

[0135] The lithium secondary battery according to the present invention can be used not only as a battery cell used as a power source for small devices but also as a unit cell in a medium or large battery module including a plurality of battery cells.

[0136] Therefore, according to one embodiment of the present invention, there are provided a battery module including a lithium secondary battery as a unit battery and a battery pack including the battery module.

[0137] According to one embodiment of the present invention, a battery module or battery pack can be used as a power source for at least one of the following medium or large devices: a power tool; an electric vehicle, including an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.

[0138] Hereinafter, examples of the present invention will be described in detail in a manner that can be easily implemented by those skilled in the art to which the present invention belongs. However, the present invention can be implemented in many different forms and should not be construed as being limited to the examples set forth herein.

[0139] Examples and Comparative Examples

[0140] Example 1

[0141] Will have Ni 0.96 Co 0.03 Mn 0.01 The transition metal composite hydroxide (D 50 : 7 μm) was sintered at 1,020° C. for 9 hours in an air atmosphere to prepare a Ni 0.96 Co 0.03 Mn 0.01 A transition metal composite oxide with a composition represented by O.

[0142] The prepared transition metal composite oxide and LiOH were mixed so that the molar ratio (Li / Me) of lithium (Li) to transition metal (Me) was 1, and the mixture was once sintered at 800° C. for 12 hours in an oxygen atmosphere, then ground using a jet mill, and secondarily sintered at 700° C. for 12 hours in an oxygen atmosphere to prepare a LiNi 0.96 Co 0.03 Mn 0.01 A positive electrode active material of a lithium transition metal composite oxide in the form of a single particle of a composition represented by O2.

[0143] Example 2

[0144] A LiNi 0.96 Co 0.03 Mn 0.01 A positive electrode active material of a lithium transition metal composite oxide in the form of a single particle of a composition represented by O2.

[0145] Example 3

[0146] A LiNi0.96 Co 0.03 Mn 0.01 A positive electrode active material of a lithium transition metal composite oxide in the form of a single particle of a composition represented by O2.

[0147] Example 4

[0148] Will have Ni 0.89 Co 0.03 Mn 0.08 The transition metal composite hydroxide (D 50 : 9 μm) was sintered at 1,020° C. for 9 hours in an air atmosphere to prepare a Ni 0.89 Co 0.03 Mn 0.08 A transition metal composite oxide with a composition represented by O.

[0149] The prepared transition metal composite oxide and LiOH were mixed so that the molar ratio (Li / Me) of lithium (Li) to transition metal (Me) was 1, and the mixture was once sintered at 900° C. for 12 hours in an oxygen atmosphere, then ground using a jet mill, and secondarily sintered at 800° C. for 12 hours in an oxygen atmosphere to prepare a LiNi 0.89 Co 0.03 Mn 0.08 A positive electrode active material of a lithium transition metal composite oxide in the form of a single particle of a composition represented by O2.

[0150] Example 5

[0151] Will have Ni 0.96 Co 0.03 Mn 0.01 The transition metal composite hydroxide (D 50 : 7 μm) was sintered at 1,020° C. for 9 hours in an air atmosphere to prepare a Ni 0.96 Co 0.03 Mn 0.01 A transition metal composite oxide with a composition represented by O.

[0152] The prepared transition metal composite oxide and LiOH were mixed so that the molar ratio (Li / Me) of lithium (Li) to transition metal (Me) was 1.05, and the mixture was primarily sintered at 800° C. for 12 hours in an oxygen atmosphere, then ground using a jet mill, and secondary sintered at 700° C. for 12 hours in an oxygen atmosphere to prepare a transition metal composite oxide having LiOH as a transition metal composite oxide. 1.05 Ni 0.96 Co 0.03 Mn 0.01A positive electrode active material of a lithium transition metal composite oxide in the form of a single particle of a composition represented by O2.

[0153] Example 6

[0154] Will have Ni 0.96 Co 0.03 Mn 0.01 The transition metal composite hydroxide (D 50 :7 μm) and LiOH are mixed so that the molar ratio (Li / Me) of lithium (Li) to transition metal (Me) is 1, and the mixture is once sintered at 830° C. for 12 hours in an oxygen atmosphere, then ground using a jet mill, and secondarily sintered at 770° C. for 12 hours in an oxygen atmosphere to prepare a LiNi 0.96 Co 0.03 Mn 0.01 A positive electrode active material of a lithium transition metal composite oxide in the form of a single particle of a composition represented by O2.

[0155] Example 7

[0156] Will have Ni 0.885 Co 0.035 Mn 0.08 The transition metal composite hydroxide (D 50 : 4.5 μm) and LiOH are mixed so that the molar ratio (Li / Me) of lithium (Li) to transition metal (Me) is 1, and the mixture is once sintered at 900° C. for 12 hours in an oxygen atmosphere, then ground using a jet mill, and secondarily sintered at 800° C. for 12 hours in an oxygen atmosphere to prepare a LiNi 0.885 Co 0.035 Mn 0.08 A positive electrode active material of a lithium transition metal composite oxide in the form of a single particle of a composition represented by O2.

[0157] Comparative Example 1

[0158] A LiNi-based composite material was prepared in the same manner as in Example 1, except that the primary sintering was performed at 700° C. instead of 800° C. and the secondary sintering was performed at 800° C. instead of 700° C. 0.96 Co 0.03 Mn 0.01 A positive electrode active material of a lithium transition metal composite oxide in the form of a single particle of a composition represented by O2.

[0159] Comparative Example 2

[0160] A LiNi 0.96 Co 0.03 Mn 0.01 A positive electrode active material of a lithium transition metal composite oxide in the form of a single particle of a composition represented by O2.

[0161] Comparative Example 3

[0162] A LiNi 0.96 Co 0.03 Mn 0.01 A positive electrode active material of a lithium transition metal composite oxide in the form of a single particle of a composition represented by O2.

[0163] Comparative Example 4

[0164] A LiNi 0.885 Co 0.035 Mn 0.08 A positive electrode active material of a lithium transition metal composite oxide in the form of a single particle of a composition represented by O2.

[0165] Experimental example

[0166] Experimental Example 1: SEM imaging and analysis of volume cumulative distribution based on particle size

[0167] The positive electrode active material precursors (as transition metal composite oxides and transition metal composite hydroxides) before being mixed with the lithium compound during the preparation of the positive electrode active materials of Examples 1 to 7 and Comparative Examples 1 to 4, and the positive electrode active materials prepared in Examples 1 to 7 and Comparative Examples 1 to 4 were each imaged using a scanning electron microscope (SEM, FEI, InspectF), and these images are shown in Figures 2 to 12 middle.

[0168] In addition, for the positive electrode active materials prepared in Examples 1 to 7 and Comparative Examples 1 to 4, a particle size analyzer (PSD, Malvern Panalytical Ltd., martersizer 3000) was used to measure the D in the volume cumulative distribution according to the particle size. 10 , D 50 , D 90 and mode, and shown in Figure 1 and Table 1, and the negative skewness value is calculated using the following formula 1 and presented together in the following Table 1.

[0169] [Formula 1]

[0170] Negative skewness = (mode - D 10 ) / D 50

[0171]

[0172] like Figures 2 to 12 As shown in , it can be confirmed that the positive electrode active materials prepared in Examples 1 to 7 and Comparative Examples 1 to 4 are all prepared as single particle positive electrode active materials defined in the present invention.

[0173] In addition, as shown in Table 1, it can be confirmed that the D 50 5 μm or more and the negative skewness calculated by Formula 1 is 0.4 or more, which confirms that the D of the positive electrode active materials prepared in Comparative Examples 3 and 4 50 Less than 5μm.

[0174] Experimental Example 2: Calendering Density Measurement

[0175] Using an automatic pelletizer (Auto Pellet Press, Carver, 3887.4), a cylindrical mold was used to adjust the zero point of the thickness for a circular particle holder with a diameter of 13 mm. Subsequently, 3 g of each positive electrode active material prepared in Examples 1 to 7 and Comparative Examples 1 to 4 was placed in a circular particle holder, and a force was applied until the force reached 9,000 kgf to measure the thickness of the formed particles. Subsequently, the particle volume was calculated using the following formula 2, the calendering density was calculated using the following formula 3, and the results are presented in Table 2 below.

[0176] [Formula 2]

[0177] Particle volume (cm 3 ) = π (radius of the circular particle holder) 2 × Particle thickness

[0178] [Formula 3]

[0179] Calendering density (g / cm 3 ) = positive electrode active material weight (g) / particle volume (cm 3 )

[0180]

[0181] As shown in Table 2, it can be confirmed that the D of the positive electrode active materials prepared in Examples 1 to 7 can be increased by adjusting the primary sintering temperature and the secondary sintering temperature. 505 μm or more, in the form of a single particle, with a fine powder amount appropriately adjusted according to the negative skewness value, and a calendering density calculated by Formula 3 of 3.56 g / cm 3 From these results, in the case of using the cathode active material according to the present invention, it is expected that the rolling density during cathode preparation can be improved to increase the energy density of the lithium secondary battery, and thus the capacity characteristics can be improved.

[0182] On the contrary, for the positive electrode active material prepared in Comparative Example 1, the secondary sintering temperature is higher than the primary sintering temperature, and for the positive electrode active material prepared in Comparative Example 2, the secondary sintering temperature is lower than the primary sintering temperature. However, since the difference between these temperatures is too large, even if D 50 5 μm or more, in the form of single particles, and the amount of fine powder according to the negative skewness value is adjusted to an appropriate level, still showing a calendering density of 3.53 g / cm 3 , therefore, it can be confirmed that this not only does not meet the minimum standard for achieving the effect according to the present invention, but also there is at least 0.06 g / cm 2 of the positive electrode active material precursor and the lithium raw material compared with Examples 1 and 2 using the same composition. 3 And at most 0.19g / cm 3 difference.

[0183] In addition, since the primary sintering temperature and the secondary sintering temperature are the same for the positive electrode active material prepared in Comparative Example 3, D 50 As shown in Table 1, the rolling density is also low. In particular, the difference in rolling density is 0.05 g / cm2 compared with Example 6 using the positive electrode active material precursor and lithium raw material of the same composition. 3 .

[0184] In addition, since the secondary sintering temperature is lower than the primary sintering temperature for the positive electrode active material prepared in Comparative Example 4, the sintering temperature of the transition metal hydroxide suitable for the positive electrode active material precursor is not sufficiently ensured, D 50 As shown in Table 1, the rolling density is also low. In particular, the difference in rolling density is 0.11 g / cm2 compared with Example 7 using the positive electrode active material precursor and lithium raw material of the same composition. 3 .

Claims

1. A positive electrode active material, the positive electrode active material comprising a lithium transition metal composite oxide in the form of single particles, the lithium transition metal composite oxide in the form of single particles containing nickel, cobalt, and manganese, in, the lithium transition metal composite oxide containing 60 mol% or more of the nickel relative to all transition metals, The lithium transition metal composite oxide has a D 50 is 5 μm or more, and When pellets were formed by applying force until the force reached 9,000 kgf using an automatic pelletizer, the pressed density of the lithium transition metal composite oxide calculated by Formula 3 was 3.56 g / cm 3 above: [Formula 3] Calendering density (g / cm 3 ) = positive electrode active material weight (g) / particle volume (cm 3 ).

2. The positive electrode active material according to claim 1, wherein the lithium transition metal composite oxide in the form of single particles being single particles or secondary particles in which 10 or fewer primary particles are aggregated.

3. The positive electrode active material according to claim 1, wherein The lithium transition metal composite oxide has an average composition represented by Chemical Formula 1: [Chemical Formula 1] Li x Ni a Co b Mr c M 1 d O2 wherein, in Chemical Formula 1, M 1 is at least one selected from the group consisting of Al, Zr, B, W, Mo, Cr, Nb, Mg, Hf, Ta, La, Ti, Sr, Ba, Ce, F, P, S, and Y, and 0.9 ≤ x ≤ 1.3, 0.6 ≤ a < 1.0, 0 < b < 0.4, 0 < c < 0.4, 0 ≤ d ≤ 0.2 and a + b + c + d = 1.

4. The positive electrode active material according to claim 3, wherein x is in the range of 0.9 to 1.

1.

5. The positive electrode active material according to claim 1, wherein The D 50 In the range of 5μm to 9μm.

6. The positive electrode active material according to claim 1, wherein The calendering density is 3.56 g / cm 3 Up to 3.80g / cm 3 within the range.

7. The positive electrode active material according to claim 1, wherein The mode in the volume cumulative distribution of particle sizes is greater than the D 50 .

8. The positive electrode active material according to claim 7, wherein The negative skewness value calculated by Formula 1 of the positive electrode active material is greater than 0: [Formula 1] Negative skewness = (mode - D 10 ) / D 50 .

9. The positive electrode active material according to claim 8, wherein the negative skewness value being in the range of 0.40 to 0.

75.

10. A positive electrode, the positive electrode comprising the positive electrode active material according to any one of claims 1 to 9.

11. A lithium secondary battery, the lithium secondary battery comprising: the positive electrode according to claim 10; a negative electrode; a separator disposed between the positive electrode and the negative electrode; and an electrolyte.

Citation Information

Patent Citations

  • Composite transition metal oxide precursor having high structural stability and preparing method thereof, and cathode active material using the same

    KR1020170119573A

  • interleukin-2 derivatives

    KR1020220113918A

Cited By

  • Positive electrode active material, method for preparing the same, and positive electrode and lithium

    CN120283311A